[Tamás Pál 6]
child with tricycle & toycar, 3 years old birthday, trabant behind the weekend house, Balaton, little black cat, cloudburst, little child in different situation, exercises in vaulting-box, 1975 Easter in the garden, school-leaving ceremony, around the weekend house, 1975 Christmas, family, New Year's Eve, sledging, 1976 4years old birthday, presents & cake, snowman &skiing, Christmas, children & grandparents,